High-level talents’ perceive overqualification and withdrawal behavior: A power perspective based on survival needs - Huang, Caiyun; Tian, Siyu; Wang, Rui; Wang, Xue (Frontiers in Psychology, 2022)
Based on the power basis theory, this study examined the relationship between high-level talents’ perceived overqualification and withdrawal behavior and the mediating role of sense of power. We also analyze the boundary effects of protected values and feeling trusted. The hypotheses of this study were tested through questionnaires gathered across three phases over three months from 371 high-level talents from 6 enterprises, 5 governments and 13 universities in China. Hierarchical regression analyses and bootstrapping appraisals showed that: (1) perceived overqualification has a positive relationship with withdrawal behavior; (2) sense of power mediates the relationship between overqualification and withdrawal behavior, with high perceived overqualification resulting in low perceived power, which then reinforces withdrawal behavior; (3) the negative relationship between perceived overqualification and sense of power is stronger for high-level talents with high protected value (as opposed to low); (4) the negative relationship between sense of power and withdrawal behavior is stronger for high-level talents with high feeling trusted (as opposed to low); (5) moderated-mediation analyses reveal that the mediating effects of sense of power are stronger for employees with high (as opposed to low) protected values or feeling trusted. At the end of this study, the theoretical and practical implications are discussed.